Participatory Communication and Digital Strategies in Environmental Advocacy: A Narrative Review of Frameworks and Impacts - Sumarni Zainuddin; Muliawan, Dadang; Trihandayani, Indah; Mambang (Sinergi International Journal of Communication Sciences, 2024)
Effective communication strategies have become indispensable in environmental advocacy amid escalating ecological crises.This narrative review explores how participatory and digital communication frameworks influence environmental awareness, public engagement, and policy transformation across varied sociopolitical contexts.Drawing on empirical literature from 2010 to 2024, sources were identified through Scopus, Google Scholar, and PubMed using terms like "environmental communication," "advocacy strategies," and "digital engagement."Studies were selected based on peer-review status, empirical relevance, and focus on participatory and multimedia approaches.The findings indicate that participatory communication, social media, narrative storytelling, and immersive technologies play pivotal roles in shaping environmental discourse and mobilizing public action.Visual and digital media significantly enhance emotional engagement, message clarity, and behavioral response. However, communication success often depends on systemic factors such as governance models (e.g., democratic vs. authoritarian regimes), economic capacity (e.g., campaign funding), and cultural alignment (e.g., values embedded in messaging). This review offers a multidimensional synthesis of participatory and technology-driven communication frameworks, highlighting policy and practice implications, particularly in low- and middle-income countries.